The role of thoracic surgery in extracorporeal membrane oxygenation services. (March 2018) - Heward, Elliot; Hashmi, Syed F; Malagon, Ignacio; Shah, Rajesh; Barker, Julian; Rammohan, Kandadai S
Background: Recent evidence surrounding the use of venovenous extracorporeal membrane oxygenation in treating acute respiratory failure has led to the expansion of extracorporeal membrane oxygenation services worldwide. The high rate of complications related to venovenous extracorporeal membrane oxygenation often requires intervention by specialist thoracic surgeons. This study aimed to investigate the role of specialist thoracic surgeons within the multidisciplinary team managing these high-risk patients. Methods: We retrospectively reviewed 90 patients who received venovenous extracorporeal membrane oxygenation at our tertiary referral center between December 2011 and May 2015. Four patients who underwent lung transplantation were excluded. Results: We found that 29.1% (25/86) of patients on venovenous extracorporeal membrane oxygenation had undergone a thoracic intervention. A total of 82 interventions were performed: 11 thoracotomies, 49 chest drains, 13 rigid bronchoscopies, 4 flexible bronchoscopies, 4 temporary endobronchial blockers, and 1 sternotomy. Of the 11 thoracotomies, 3 were reexplorations. Survival to discharge for patients who underwent thoracic surgical interventions was 72% (18/25). Conclusions: Our experience has demonstrated that a large proportion of patients receiving venovenous extracorporeal membrane oxygenation require a thoracic intervention, many of which are major intraoperative procedures. Patients on venovenous extracorporeal membrane oxygenation have benefited from rapid on-site access to thoracic surgical services to manage these challenging life-threatening complications.